Insulin-Like Growth Factor Binding Protein-3 (IGFBP-3): Unraveling the Role in Mediating IGF-Independent Effects Within the Cell - Varma Shrivastav, Shailly; Bhardwaj, Apurva; Pathak, Kumar Alok; Shrivastav, Anuraag (Frontiers in Cell and Developmental Biology, 2020)
Insulin-like growth factor (IGF) binding protein-3 (IGFBP-3), one of the six members of the IGFBP family, is a key protein in the IGF pathway. IGFBP-3 can function in an IGF-dependent as well as in an IGF-independent manner. The IGF-dependent roles of IGFBP-3 include its endocrine role in the delivery of IGFs from the site of synthesis to the target cells that possess IGF receptors and the activation of associated downstream signaling. IGF-independent role of IGFBP-3 also includes its interactions with the proteins of the extracellular matrix and the proteins of the plasma membrane, its translocation through the plasma membrane into the cytoplasm and into the nucleus. The C-terminal domain of IGFBP-3 has the ability to undergo cell penetration therefore, generating a short 8-22-mer C-terminal domain peptides that can be conjugated to drugs or genes for effective intracellular delivery. This has opened doors for biotechnological applications of the molecule in molecular medicine. The aim of this this review is to summarize the complex roles of IGFBP-3 within the cell, including its mechanisms of cellular uptake and its translocation into the nucleus, various molecules with which it is capable of interacting, and its ability to regulate IGF-independent cell growth, survival and apoptosis. This would pave way into understanding the modus operandi of IGFBP-3 in regulating IGF-independent processes and its pleiotropic ability to bind with potential partners thus regulating several cellular functions implicated in metabolic diseases, including cancer.